The needs for media development of Porlite (literacy portal) via Google Sites to increase the student’s reading interest - Rafniati, Rafniati; Dahri, Nuraeni (PT The Collaboration UVW, 2024)
This research aimed to analyze the needs for media development of a portal media (literacy portal) via the Google Site to increase student’s interest in reading. The portal media is called Porlite. Porlite can be used to increase the ability to use digital technology in the world of education, especially during the implementation of school literacy movements. This portal media via the Google site can also increase student’s interest in reading and literacy skills. This type of research was quantitative-descriptive. The research subjects were students of SMAN 1 Pulau Punjung. This research took a sample of 73 students from 286 populations in phase E. The research results showed that student’s interest in Porlite was 80%, while the needs for students to use Porlite as a literacy medium was 70%, and the relationship between Porlite and interest in reading was 72%. Porlite with Google Sites can be used in literacy activities to increase student’s interest in reading.